Effect of direct water injection temperature on combustion process and thermal efficiency within compression ignition internal combustion Rankine engine. (December 2021) - Kang, Zhe; Feng, Shangsi; Lv, Yang; Wu, Jingtao; Wu, Zhijun
Abstract: Compression ignition-internal combustion Rankine cycle (CI-ICRC) concept implement oxy-fuel combustion, direct water injection (DWI) and waster heat recovery into traditional diesel cycle to realize ultra-high thermal efficiency and low emission powertrain. As indicated by ICRC concept, the DWI process show critical impact on its combustion process and thermal efficiency. This paper dedicated in investigating the effect of different DWI temperature on cycle performance and thermal efficiency within prototype CI-ICRC engine, in order to do so, independent DWI system, O2 /CO2 intake system and reconfigurable electronic controller is established. Combustion characteristics including in-cylinder pressure, heat release rate, combustion stability, brake thermal efficiency are experimentally investigated. The cycle performance and thermal efficiency are proved to be optimized under elevated DWI temperature, an optimum 46.6% brake thermal efficiency is achieved, while the coefficient of variation remains around 1%. The NOX and soot emissions are both reduced under DWI utilization, the mechanism of soot reduction is highly related to thermolysis of water or carbon-water reactions which further chemical kinetic analysis is needed. The result of this study provides fundamental information for future CI-ICRC engine optimization, and can also be utilized in providing reference guidance for DWI implementation within modern internal combustion engines.